The influence of medical and nonmedical factors to the progression of renal osteodystrophy - Šubat-Dežulović, Mirna (Array, 2009)
Abstract: We report a 13-year-old boy hospitalized for the first time at the age of 17 months with clinical and laboratory signs of chronic kidney disease (CKD) and renal osteodystrophy caused by severe obstructive uropathy of the single kidney. Prevention and treatment of renal osteodystrophy has been target for aggressive therapy and the great challenge for pediatric nephrologists. The outcome of the therapy of renal osteodystrophy is influenced by medical and non – medical factors. It was concluded that the place of living (in our example a small village distant from primary care physicians, far from the social care professionals and far from the hospital), inferior social and economical status with inadequate nutrition present negative factors that contributed to the outcome and development of CKD and its complications as is renal osteodystrohy. The coordination of medical and non – medical professionals is necessary on the primary and secondary level to achieve positive results of therapy in patients with CKD